GIS-material for the archaeological project: St. Olai cemetery - District cooling through central Norrköping - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
During winter 2004 and spring 2005 the Swedish National Heritage Board's Contract Archaeology Division, UV Öst, performed a field evaluation in central Norrköping, due to trenching works for district cooling. The trenching affected the medieval and early modern city layers, RAÄ 96. Both cultural layers from the 17th and 18th century and graves from the Middle Ages and the early modern period, belonging to Saint Olai church, were found. Waste and demolition layers as well as ground preparation layers were found on Skolgatan street. Part of the street has probably been located only a block away from Saint Olai church during the late Middle Ages/early modern period. The layers date to the 17th century, both from before and after the street regulation that took place during the second part of the century. No traces of older street stretches or of the known city fires were found. South-east of the church, graves from the medieval and early modern cemetery were discovered. A ditch west of the graves might represent the cemetery's limit. On Kristinagatan street the land has first been used for farming during the 17th century, and later a building has stood here. Fragmented agricultural layers from the late 18th century were found on a short stretch of Knäppingsborgsgatan street. On the rest of the street, as well as on Östra Promenaden street, any possible archaeological remains had been removed during earlier earthworks.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to document and interpret possible archaeological remains, and to put the results into a relevant culture-historical context.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst utförde vintern 2004/våren 2005 en förundersökning i form av antikvarisk kontroll genom centrala Norrköping. Anledningen var ett schaktningsarbete för fjärrkyleledning. Detta berörde medeltida och efterreformatoriska stadslager, RAÄ 96. Vid förundersökningen påträffades kulturlager från 1600-1700-tal, samt medeltida och efterreformatoriska gravar tillhörande S:t Olai kyrka. I Skolgatan väster om Drottninggatan fanns avfalls- och raseringslager troligen från stadsgårdar. Lagren dateras till tiden både före och efter gaturegleringen under 1600-talets andra hälft. Det påträffades inga spår efter äldre gatusträckningar eller de kända stadsbränderna i Norrköping. I Skolgatan öster om Drottninggatan kunde markberednings- och raseringslager iakttas som troligen varit belägna inom ett kvarter söder om S:t Olai kyrkogård under senmedeltid/efterreformatorisk tid. Sydöst om den nuvarande kyrkan påträffades gravar från den medeltida och efterreformatoriska kyrkogården. Möjligen utgör ett dike en form av kyrkogårdsbegränsning strax väster om gravarna. Få äldre lämningar iakttogs i Kristinagatan och Knäppingsborgsgatan. I Kristinagatan har marken tagits i bruk troligen under 1600-talet i samband med odling men senare utnyttjats som gårdstomt. Vid endast en kort sträcka i Knäppingsborgsgatan påträffades fragmentariska odlingslager från sent 1700-tal. Större delen av Knäppingsborgsgatan och Östra Promenaden var i övrigt utschaktad.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den nu aktuella förundersökningen var att dokumentera och tolka eventuella äldre berörda lämningar, samt att sätta in resultaten i ett relevant kulturhistoriskt sammanhang.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: S:t Olai kyrkogård - Fjärrkyla genom centrala Norrköping
Keywords: historical period; historisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi